Socio-cultural transformation of Ukraine in the context of European values - Nosyriev, O. O.; Bukina, T. (LLC Publishing House "Baltija Publishing", Latvia, 2021)
The article considers the issues of changing accents and cultural transformation in Ukraine, Great Britain and other European countries. In recent years, Ukraine has seen an active revival in the cultural sphere. From publishing to music, from film production to theater, from fashion to curatorial exhibitions – the Ukrainian cultural environment has become bold, diverse and large-scale. Euromaidan has given impetus to a powerful wave of cultural activism: from discussion platforms to spontaneous exhibitions, from urban regeneration projects to volunteer groups seeking to protect dilapidated national heritage sites. The impetus for it was the dynamism of the Ukrainian creative community. And further development became possible thanks to the support of new state cultural institutions. These institutes emerged after Euromaidan, such as the Ukrainian Cultural Foundation, the Ukrainian Book Institute, and the Ukrainian Institute. Institutions with a long history, such as the State Agency of Ukraine for Cinema, have strengthened their positions. The creation of these new institutions marked the departure from the post-Soviet system of cultural management. And the transition to a consistent and comprehensive cultural policy. The main thing is that the creation of a new system of culture in Ukraine has helped to bridge the gap between the state and cultural activists and the creative sector. One of the most important problems of the cultural sector in Ukraine for the last 25 years is funding. This problem is also relevant for the United Kingdom. But when it comes to finding resources for artists and cultural institutions, British policy has a respectable tradition and a number of successful answers. Support for the arts by both the state and business seems to be a matter of course for the British. At the same time, the idea of the self-worth of art is also supported by the idea of its social significance, as well as the perception of art as a primary source of creativity, innovative development, creative industry. The relationship between the European Union and the society of Ukraine is already yielding some results in the context of ensuring the democratic and European development of the state. For the successful implementation of European integration in Ukraine, it is necessary to apply such mechanisms that will ensure coordinated management of social processes of the state in the direction of European integration. The main mechanism is cultural policy, which should be aimed at regulating the regulatory framework. And the application of regulations in practice. This will allow culture to take a leading position on the path to national modernization. Legislation should be a mechanism for achieving goals, and the main thing should remain that the person should be at the center of cultural policy of the state. Given the experience of the United Kingdom, the formation of Ukraine's cultural policy should be based on the idea of the all-encompassing impact of culture on modern society. Accordingly, such a policy, being aimed at the cultural sector, effectively affects all spheres of public life. Consistent support for culture at the financial and fiscal, legislative and executive, national and local levels should, above all, be based on an awareness of the value of culture. Culture enriches people's lives, changes their worldview and inspires creativity. In the social dimension, its impact has the most significant impact on education, health and cohesion.

У статті розглядаються питання зміни акцентів і культурної трансформації в Україні, Великій Британії та інших країнах Європи. В останні роки в Україні спостерігається активне пожвавлення культурної сфери. Від видавничої справи до музики, від кіновиробництва до театру, від моди до кураторських виставок – українське культурне середовище стало сміливим, різноманітним і масштабним. Євромайдан дав поштовх потужній хвилі культурного активізму: від дискусійних майданчиків до спонтанних виставок, від проєктів відродження міст до волонтерських груп, які прагнуть захистити напівзруйновані об’єкти національної спадщини. Поштовхом до нього став динамізм української творчої спільноти. А подальший розвиток став можливим завдяки підтримці нових державних закладів культури. Ці інститути виникли після Євромайдану, як Український культурний фонд, Український інститут книги, Український інститут. Зміцнили свої позиції інституції з багаторічною історією, такі як Державне агентство України з питань кіно. Створення цих нових установ ознаменувало відхід від пострадянської системи управління культурою. І перехід до послідовної та комплексної культурної політики. Головне, що створення нової системи культури в Україні допомогло подолати прірву між державою та культурними діячами та креативним сектором. Однією з найважливіших проблем сфери культури в Україні за останні 25 років є фінансування. Ця проблема актуальна і для Великобританії. Але коли йдеться про пошук ресурсів для митців і культурних установ, британська політика має поважну традицію та низку успішних відповідей. Підтримка мистецтва як державою, так і бізнесом для британців, схоже, є чимось зрозумілим. Водночас ідея самоцінності мистецтва підкріплюється також ідеєю його суспільної значущості, а також сприйняття мистецтва як першоджерела творчості, інноваційного розвитку, креативної індустрії. Відносини Європейського Союзу та суспільства України вже дають певні результати в контексті забезпечення демократичного та європейського розвитку держави. Для успішної реалізації європейської інтеграції в Україні необхідно застосовувати такі механізми, які забезпечуватимуть узгоджене управління суспільними процесами держави в євроінтеграційному напрямку. Основним механізмом є культурна політика, яка має бути спрямована на врегулювання нормативно-правової бази. І застосування нормативних актів на практиці. Це дозволить культурі зайняти провідні позиції на шляху національної модернізації. Законодавство має бути механізмом досягнення цілей, а головним має залишатися те, щоб у центрі культурної політики держави була людина. Враховуючи досвід Великої Британії, формування культурної політики України має базуватися на ідеї всеосяжного впливу культури на сучасне суспільство. Відповідно, така політика, маючи спрямування на культурну сферу, ефективно впливає на всі сфери суспільного життя. Послідовна підтримка культури на фінансово-податковому, законодавчому та виконавчому, національному та місцевому рівнях має ґрунтуватися, перш за все, на усвідомленні цінності культури. Культура збагачує життя людей, змінює їхній світогляд і надихає на творчість. У соціальному вимірі його вплив найбільше впливає на освіту, здоров'я та згуртованість.
Соціокультурна трансформація України в контексті європейських цінностей
Keywords: culture; cultural policy; state cultural policy; socio-cultural transformation; European values; культурна політика; культура; державна культурна політика; соціокультурна трансформація; європейські цінності